2022
DOI: 10.1177/02692163221102266
|View full text |Cite
|
Sign up to set email alerts
|

Health care professionals’ perceptions of factors influencing the process of identifying patients for serious illness conversations: A qualitative study

Abstract: Background: The Serious Illness Care Programme enables patients to receive care that is in accordance with their priorities. However, despite clarity about palliative care needs, many barriers to and difficulties in identifying patients for serious illness conversations remain. Aim: To explore healthcare professionals’ perceptions about factors influencing the process of identifying patients for serious illness conversations. Design: Qualitative design. A thematic analysis of observations and semi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The need to adapt identification methods was recognized for specific settings (e.g., units or departments), as well as for different patient groups (e.g., based on diagnosis) and patient conditions (e.g., illness progression, mental and physical health status). In past research, Swedish physicians and nurses described ethical and existential obstacles in identifying patients for SIC with regard to timing, relationships and attitudes [ 25 ]. A recent scoping review showed that patient identification for SIC can be undertaken in various ways and by different clinicians, including physicians, nurses, and allied health [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to adapt identification methods was recognized for specific settings (e.g., units or departments), as well as for different patient groups (e.g., based on diagnosis) and patient conditions (e.g., illness progression, mental and physical health status). In past research, Swedish physicians and nurses described ethical and existential obstacles in identifying patients for SIC with regard to timing, relationships and attitudes [ 25 ]. A recent scoping review showed that patient identification for SIC can be undertaken in various ways and by different clinicians, including physicians, nurses, and allied health [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Development of routines for patient identification should be undertaken on-site by clinicians, with consideration given to practice culture and patient population [ 27 ]. This means that identification strategies should be evaluated and refined during the implementation process [ 27 ] to identify the right patient at the right time instead of adopting a one-size fits-all approach [ 25 ]. Processes such as these can be impacted by structural characteristics and clinical culture aspects within the inner setting of an organization [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open access their perception of whether it was the 'right' time to talk about certain issues have been found to impact the ways in which patients were identified for serious illness conversations. 18 It is therefore important to examine clinician perceptions surrounding communication initiatives, as personal or professional outlooks can impact the success of implementations in practice. This study aimed to explore physicians' perceptions regarding the impact of serious illness conversations on patients.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…After the implementation, the need to expand the SICP to include nurses was highlighted, with a focus on team collaboration and sustainable organizational structures. 16,17 To make the SICP suitable for the Swedish context, it is necessary to translate, adapt, and validate the SICG in Swedish. This study therefore aimed to translate and adapt the SICG for use within the Swedish healthcare setting and examine the validity and acceptability of the Swedish SICG.…”
Section: Introductionmentioning
confidence: 99%